Development Of Audiovisual Learning Media Technosociopreneur Based On Social Studies Subjects In Elementary Schools - Rudi Ritonga; Sulistyani Puteri Ramadhani; Myviani Christin Ananda Palit (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study aims to develop audiovisual learning media based on social science and social studies subjects in Class IV Elementary Schools and to find out student responses after carrying out the learning process using audiovisual learning media. To find out the students' responses after carrying out the learning prozy by using technosociopreneur-based audiovisual learning media. The issledovaniya i razrabotki (R & D) method with the ADDIE framework (Analiz, Dizayn, Razrabotka, Vnedreniye, Dan Otsenka). SMI learning is carried out by validation tests for SMI experts and material experts. After being tested by a team of experts, a product trial was then carried out with class IV research subjects at SDN 01 Kuningan, South Jakarta. The test results of technosociopreneur-based audio-visual learning media obtained an average expert validation score of 85.00% so that it received the «very feasible» category and the product trial results (limited product trials) received an average score of 81.46% with category «very good». So, it can be concluded that techno-sociopreneur-based audio visual learning media is feasible and can be used.